Scanned versus Fused-Reconstructed Oblique MR-Images for Assessment of the Tibiofibular Syndesmosis-Diagnostic PerFormance and Reader Agreement - Seuß, Hannes; Hammon, Matthias; Roemer, Frank; Heiß, Rafael; Janka, Rolf Matthias; Uder, Michael; Dankerl, Peter (Diagnostics, 2021)
To evaluate the diagnostic performance and reader agreement of a novel MRI image fusion method enabling the reconstruction of oblique images for the assessment of the tibiofibular syndesmosis. We evaluated 40 magnetic resonance imaging examinations of patients with ankle sprains (16 with ruptures and 24 without) for the presence of anteroinferior tibiofibular ligament rupture. For all patients, we performed a fusion of standard two-dimensional transversal and coronal 3 mm PDw TSE images into an oblique-fusion reconstruction (OFR) and compared these against conventionally scanned oblique sequence for the evaluation of the tibiofibular syndesmosis. To evaluate diagnostic performance, two expert readers independently read the OFR images twice. We analyzed sensitivity, specificity, negative and positive predictive values, accuracy, and agreement. Reader 1 misinterpreted one OFR as a false negative, demonstrating a sensitivity of 0.94 and specificity of 1.00, reader 2 demonstrated perfect accuracy. Intrareader agreement was almost perfect for reader 1 (alpha = 0.95) and was perfect for reader 2 (alpha = 1.00). Additionally, interreader agreement between all fusion sequence reads was almost perfect (alpha = 0.97). The proposed OFR enables reliable detection of anteroinferior tibiofibular ligament rupture with excellent inter- and intrareader agreement, making conventional scanning of oblique images redundant and supplies a method to retroactively create oblique images, e.g., from external examinations.
CRIS-Team WoS Importer:2021-03-19